Gerakan Literasi Internasionalisasi Perguruan Tinggi di Pesantren Internasional - Winarni, Leni; Minasari, Arofah; Purwasito, Andrik (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2022)
Modernity demands a high-quality human being, especially education. While part of society justifies that the best education should have an international label since it is considered to master many things. Therefore is not surprising that many parties have created international labeled schools in Indonesia, such as  Islamic boarding schools. They are marked with the term “Islamic International Boarding School” and have a primary vision and mission to deliver the students (santri) able to compete in the international realm. However, understanding literacy to obtain information, especially about getting information sources, studies programs following the students' expertise, and so on, is still limited. Drawing from these problems, we held a community service activity, which focused on an information literacy campaign held in Islamic International School Sabilil Muttawien, Magetan, East Java. This activity aims to find out the description of literacy about the internationalization of higher education. Based on this background, we also survey how the santri seek information about international higher education that santri will be able to use online media as santri (prospective students) can find out detailed information about top international universities.